Full-stack web development with Go build your web applications quickly using the Go programming language and Vue.js - Tolaram, Nanik; Glynn, Nick (Packt Publishing Ltd., 2023)
A Go programmer's hands-on guide to go from building basic server-side templates to full single page apps using Tailwind CSS, Vue.js, and more Key Features Learn how to structure your Go projects, be smarter with SQLc, create middleware and secure your apps Explore different frontend frameworks and dive into Vue and Tailwind CSS Use Terraform and Docker and deploy in minutes Book Description Go is a modern programming language with capabilities to enable high-performance app development. With its growing web framework ecosystem, Go is a preferred choice for building complete web apps. This practical guide will enable you to take your Go skills to the next level building full stack apps. This book walks you through creating and developing a complete modern web service from auth, middleware, server-side rendering, databases, and modern frontend frameworks and Go-powered APIs. You'll start by structuring the app and important aspects such as networking, before integrating all the different parts together to build a complete web product. Next, you'll learn how to build and ship a complete product by starting with the fundamental building blocks of creating a Go backend. You'll apply best practices for cookies, APIs, and security, and level up your skills with the fastest growing frontend framework, Vue. Once your full stack application is ready, you'll understand how to push the app to production and be prepared to serve customers and share it with the world. By the end of this book, you'll have learned how to build and ship secure, scalable, and complete products and how to combine Golang with existing products using best practices. What you will learn Discover how to quickly scaffold, structure, and build your Golang applications Design and build databases using PostgreSQL and SQLc to generate type-safe SQL code Monitor applications with centralized logging and metrics collection for high performance Explore frontend frameworks and libraries such as Vuetify, Buefy, and Tailwind CSS to build a responsive frontend for your app Communicate securely between the frontend and backend with cookies and session handling with middleware Understand how to package applications using Docker and set up CI pipelines in GitHub Who this book is for This book is for Go programmers who want to combine the power of the Go language with modern web development technologies to build complete web apps from frontend to backend. The book assumes beginner-level knowledge of HTML, CSS, and the web.